Quantification of Facial Allograft Edema During Acute Rejection: A Software-Based 3-Dimensional Analysis. Issue 3 (September 2022) - Boczar, Daniel; Brydges, Hilliard; Rodriguez Colon, Ricardo; Onuh, Ogechukwu C.; Trilles, Jorge; Chaya, Bachar F.; Gelb, Bruce; Ceradini, Daniel J.; Rodriguez, Eduardo D.
Abstract : Background: Acute rejection (AR) is a common complication in facial transplant (FT) patients associated with allograft edema and erythema. Our study aims to demonstrate the feasibility of using software-based 3-dimensional (3D) facial analysis to quantify edema as it resolves during/after AR treatment in an FT patient. Methods: Our patient is a 23-year-old man who underwent a face and bilateral hand allotransplant in August 2020. The Vectra H1 (Canfield, Fairfield, NJ) portable scanner was used to capture 3D facial images at 8 time points between postoperative day (POD) 392 and 539. The images were analyzed with the Vectra Software using a rejection-free image (POD 539) as a control. Results: Edema increased in the periorbital, lower third, and submandibular regions before AR treatment (POD 392–415). At POD 448, total facial edema was reduced to near baseline values in response to plasmapheresis and thymoglobulin (+156.94 to +28.2 mL). The fastest and most notable response to treatment was seen in the periorbital region, while some edema remained in the submandibular (+19.79 mL) and right lower third (+8.65 mL) regions. On POD 465, after the initial improvement, the edema increased but was resolved with steroid use. Facial edema did not correlate with the histopathological evaluation in our patient. Conclusions: We demonstrated the feasibility of analyzing 3D facial images to quantify edema during/after AR treatment in an FT patient. Our analysis detected edema changes consistent with AR followed by an improvement after treatment. This technology shows promise for noninvasive monitoring of FT patients.